EXPLORING THE DERIVATIONAL PRINCIPLE IN LINGUISTICS: A COMPREHENSIVE REVIEW - Matkurbanova Yulduz Urazimbetovna (Galaxy International Interdisciplinary Research Journal, 2024)
The derivational principle stands as a fundamental concept in linguistics, governing the formation and evolution of words across languages. This article provides a comprehensive review of the derivational principle, exploring its theoretical foundations, practical applications, and significance in linguistic analysis. Drawing on a wide range of scholarly sources, including seminal works and recent research findings, this review elucidates the various aspects of the derivational principle, from its role in morphological analysis to its implications for language acquisition and typology. Furthermore, the article discusses the methodological approaches employed in studying derivational processes and examines the challenges and controversies surrounding this area of linguistic inquiry. By synthesizing existing knowledge and highlighting emerging trends, this review contributes to a deeper understanding of the derivational principle and its importance in the study of language structure and evolution.